Phorbol 12-myristate 13-acetate and insulin increase the concentration of fructose 2,6-bisphosphate and stimulate glycolysis in chicken embryo fibroblasts. - Bosca, L (1985)
Incubation of chicken embryo fibroblasts with mitogenic concentrations of insulin for 24 hr or with the tumor promoter phorbol 12-myristate 13-acetate for 6 hr stimulated lactate release and 3-O-methylglucose uptake. Insulin also increased the Vmax of 6-phosphofructo-1-kinase (ATP:D-fructose-6-phosphate 1-phosphotransferase, EC 2.7.1.11). Both agents increased the concentration of fructose 2,6-bisphosphate and the activity of 6-phosphofructo-2-kinase (EC 2.7.1.-), the enzyme that catalyzes the synthesis of this stimulator of 6-phosphofructo-1-kinase. These changes provide an explanation for the stimulation of glycolysis by insulin and phorbol esters. In contrast to the situation in rat liver, fructose 2,6-bisphosphate concentration did not decrease after cyclic AMP treatment. Incubation of cells with phorbol ester analogues or with glycerol derivatives that are known to stimulate, or to bind to, protein kinase C did increase the concentration of fructose 2,6-bisphosphate, suggesting that the stimulation of 6-phosphofructo-2-kinase by phorbol 12-myristate 13-acetate is mediated by protein kinase C.